2015
DOI: 10.4049/jimmunol.1401046
|View full text |Cite
|
Sign up to set email alerts
|

Contact-Dependent Depletion of Hydrogen Peroxide by Catalase Is a Novel Mechanism of Myeloid-Derived Suppressor Cell Induction Operating in Human Hepatic Stellate Cells

Abstract: Myeloid-derived suppressor cells (MDSC) represent a unique cell population with distinct immunosuppressive properties that have been demonstrated to shape the outcome of malignant diseases. Recently, human hepatic stellate cells (HSC) have been reported to induce monocytic-MDSC from mature CD14+ monocytes in a contact-dependent manner. We now report a novel and unexpected mechanism by which CD14+HLADRlow/− suppressive cells are induced by catalase-mediated depletion of hydrogen peroxide (H2O2). Incubation of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…146 In mice, activated HSCs can induce expansion and accumulation of MDSCs derived from myeloid progenitor cells, which is mediated by IL-6, 149 CD44, complement component 3, 150 COX-2, and catalase-mediated depletion of hydrogen peroxide. [151][152][153][154] Also, HSC-derived SDF-1 plays a crucial role in MDSC migration in the mouse HCC model. 155 Based on these findings, preventing MDSC induction and infiltration could be an effective strategy for HCC therapy.…”
Section: Decorinmentioning
confidence: 99%
“…146 In mice, activated HSCs can induce expansion and accumulation of MDSCs derived from myeloid progenitor cells, which is mediated by IL-6, 149 CD44, complement component 3, 150 COX-2, and catalase-mediated depletion of hydrogen peroxide. [151][152][153][154] Also, HSC-derived SDF-1 plays a crucial role in MDSC migration in the mouse HCC model. 155 Based on these findings, preventing MDSC induction and infiltration could be an effective strategy for HCC therapy.…”
Section: Decorinmentioning
confidence: 99%
“…In another study, it was indicated that monocytic MDSCs are induced by catalase-mediated exhaustion of hydrogen peroxide from mature CD14+ monocytes, and the frequency of MDSC inversely correlated with hydrogen peroxide level. The oxidative stress in many liver diseases with decreased activity of catalase and increased hydrogen peroxide might inhibit the expansion and activation of hepatic MDSCs that are expected to resolve overimmune response [138]. Therefore, oxidative stress might serve as a mediator of impeding immune suppression response to promote inflammation.…”
Section: Immune Suppression: a Potential Linkage Of Oxidative Strementioning
confidence: 99%
“…This HSC-monocyte interaction results in early tumor recurrence and poor survival of liver cancer patients (Ji, et al, 2015). Moreover, they can induce the contact-dependent accumulation of MDSC, either through CD44 on HSC or through hydrogen peroxide depletion by catalase (Hochst, et al, 2013; Resheq, et al, 2015). HSC can also directly trigger T cell dysfunction through pathways analogous to other immunosuppressive cells.…”
Section: Cells Of the Hepatic Tumor Environment And Their Regulatimentioning
confidence: 99%